THE INFLUENCE OF THE UTILIZATION COMPUTER MEDIA AND VISUAL MEDIA TOWARD MATHEMATICS LEARNING OUTCOMES OF STUDENT GRADE VII AT SMP MUHAMMADIYAH 2 KALASAN - Dita Ismiasih; Suparman Suparman (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2017)
This research was done because there are many students who are less active, less enthusiastic in the learning process and fewer utilization media that the learning outcomes obtained are less optimal. This research aims to determine the influence of the utilization of computer media and visual media toward mathematics learning outcomes of students' grade VII at SMP Muhammadiyah 2 Kalasan Sleman of even semester in the academic year 2015/2016. This was the control group posttest only. The population in this research were students class VII SMP Muhammadiyah 2 Kalasan district Sleman. Samples were taken using random sampling techniques derived from class VII D as an experimental class and class VII E as the control class. The data collection is done with the test method. A testing instrument using validity and reliability. Data were analyzed using analysis prerequisite tests including normality test with the formula Chi-Kuadrat, homogeneity test by test Bartlett, and hypothesis testing with t-test. Based on calculations by the significant level  5% and the degrees of freedom 54, we concluded that: (1) There are differences in learning outcomes of students using computer media and using visual media. This is indicated by the results of the first test of the hypothesis that  2,040  >  = 2,005 (2) learning using computer medial is more effective than learning using visual media. It is shown on the second hypothesis that the test results  2,040 >  = 1,674.